Nothing like it in the world : the men who built the transcontinental railroad, 1863-1869 - Ambrose, Stephen E. (New York : Simon & Schuster, 2000)
The account of an unprecedented feat of engineering, vision, and courage. It is the story of the men who built the transcontinental railroad-the investors who risked their businesses and money; the enlightened politicians who understood its importance; the engineers and surveyors who risked, and sometimes lost, their lives; and the Irish and Chinese immigrants, the defeated Confederate soldiers, and the other laborers who did the backbreaking and dangerous work on the tracks. The U.S. government pitted two companies, the Union Pacific and the Central Pacific Railroads, against each other in a race for funding, encouraging speed over caution. At its peak, the work force approached the size of Civil War armies, with as many as 15,000 workers on each line. Nothing like this great work had ever been seen in the world when the golden spike was driven in Promontory Peak, Utah, in 1869, as the Central Pacific and the Union Pacific tracks were joined. This is the story of the brave men, the famous and the unheralded, ordinary men doing the extraordinary -- who accomplished the spectacular feat that made the continent into a nation.
ch. 1. Picking the route 1830-1860 -- ch. 2. Getting to California 1848-1859 -- ch. 3. Birth of the Central Pacific 1860-1862 -- ch. 4. Birth of the Union Pacific 1862-1864 -- ch. 5. Judah and the elephant 1862-1864 -- ch. 6. Laying out the Union Pacific line 1864-1865 -- ch. 7. Central Pacific attacks the Sierra Nevada 1865 -- ch. 8. Union Pacific across Nebraska 1866 -- ch. 9. Central Pacific assaults the Sierra 1866 -- ch. 10. Union Pacific to the Rocky Mountains 1867 -- ch. 11. Central Pacific penetrates the summit 1867 -- ch. 12. Union Pacific across Wyoming 1868 -- ch. 13. Brigham Young and the Mormons make the grade 1868 -- ch. 14. Central Pacific goes through Nevada 1868 -- ch. 15. Railroads race into Utah January 1-April 10, 1869 -- ch. 16. To the summit April 11-May 7, 1869 -- Done May 8-10, 1869.
Includes bibliographical references (p. 407-411) and index.
Keywords: Railroads -- United States -- History -- 19th century; Central Pacific Railroad Company -- History; Union Pacific Railroad Company -- History; Railroad construction workers -- United States -- History -- 19th century; Union Pacific Railroad Company; Central Pacific Railroad; USA